Emerging genomic biomarkers in migraine. (January 2013) - Menon, Saras; Griffiths, Lyn
Migraine is a debilitating neurovascular condition classified as either migraine with aura or migraine without aura. A significant genetic basis has been implicated in migraine and has probed the role of neurotransmitters, hormones and vascular genes in this disorder. The aim of this review is to highlight the recent genetic discoveries contributing to our understanding of the complex pathogenesis of migraine. The current review will discuss the role of neurotransmitter-related genes in migraine, including the recently identified TRESK and variants of the KCNN3 gene, as well as outlining studies investigating hormone receptor genes, such as ESR1 and PGR, and vascular-related genes, including the MTHFR and NOTCH 3 genes.